Impact of built, social, and economic environments on adolescent obesity and related health behaviors. Issue 4 (21st March 2023) - Prados, María J.; Nicosia, Nancy; Datar, Ashlesha
Abstract: Objective: This study aimed to estimate the effects of the built, social, and economic environments on adolescent obesity and related behaviors. Methods: Exploiting quasi‐exogenous variation in military families' geographic location, this study estimated intent‐to‐treat models of the association between the assigned installation's county environments and adolescents' (mean age 13.5 years) self‐reported and model‐corrected BMI, overweight or obesity status, and self‐reported diet and exercise. Three indices for the built, social, and economic environments characterized county‐level environments (higher value implies more advantageous environments) based on 19 indicators. Multivariate linear and logistic models were estimated on the full sample ( N =  1111) and on subsamples with greater exposure based on time ( n  = 682) and off‐installation residence ( n  = 604). Results: Exposure to more advantageous built environments for more than 2 years was associated with lower probabilities of obesity (−0.18; 95% CI: −0.34 to −0.026) and overweight or obesity (−0.34; 95% CI: −0.56 to −0.12) and was associated with lower BMI z scores (−0.76; 95% CI: −1.45 to −0.02). Results for adolescents living off‐installation were similar. More advantageous built environments were also associated with lower consumption of unhealthy foods, but not with physical activity. Social and economic environments were not associated with any outcomes. Conclusions: The built environment, but not social and economic environments, was a strong predictor of adolescents' BMI, overweight or obesity status, and eating behaviors.